2009
DOI: 10.1007/s11666-009-9371-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Corrosion Studies of HVOF-Sprayed Cr3C2-NiCr Coating on SAE-347H Boiler Steel

Abstract: Cr 3 C 2 -NiCr coating was deposited on SAE-347H boiler steel by high velocity oxy fuel (HVOF) spray process. Subsequently, high-temperature corrosion behavior of the bare and coated boiler steel was investigated at 700°C for 50 cycles in Na 2 SO 4 -82Fe 2 (SO 4 ) 3 molten salt, as well as air environments. Weight-change measurements after each cycle were made to establish the kinetics of corrosion. X-ray diffraction, field emission-scanning electron microscopy/energy dispersive spectroscopy, and x-ray mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Chromium carbide-based materials are generally employed to produce hard coatings for high temperature wear applications including sliding, fretting, abrasion, and erosion in powder generation industry, aerospace industry, oil-refining industry, heat-treatment rolls, and coal burning boiler tubes [1,2]. The chromium carbides-nickel chromium (Cr 3 C 2 -NiCr) cermet coatings have been widely practiced in industry, caused by the advantageous combination of Cr 3 C 2 ceramic phase with good wear-resistance and NiCr metal phase which provides high oxidation resistance to high temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chromium carbide-based materials are generally employed to produce hard coatings for high temperature wear applications including sliding, fretting, abrasion, and erosion in powder generation industry, aerospace industry, oil-refining industry, heat-treatment rolls, and coal burning boiler tubes [1,2]. The chromium carbides-nickel chromium (Cr 3 C 2 -NiCr) cermet coatings have been widely practiced in industry, caused by the advantageous combination of Cr 3 C 2 ceramic phase with good wear-resistance and NiCr metal phase which provides high oxidation resistance to high temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The FE-SEM analysis (Figure 3(a)) from the surface also validates the presence of Fe and O on the surface of the sample, which is further confirmed by EDS analysis from the cross-section in Figure 4(a), which shows Fe in very high percentage at points 3, 4, 5, 6 and 7 of the oxide scale layer along with a sufficient amount of O, indicating the formation of iron oxide. Formation of such types of oxide has also been analyzed by Sidhu et al, [3] Prakash et al, [23] Srikanth et al, [24] Singh, [25] Bala, [26] Kaushal et al, [27] and Kaur et al [28] . The presence of Fe 2 O 3 is further confirmed by EPMA analysis (Figure 5).…”
Section: A Uncoated T-91 Steelmentioning
confidence: 99%
“…The cyclic hot corrosion studies create the severest conditions for testing, which simulate the conditions prevailing in actual service environment of the superalloy components, where breakdown/shutdown occurs frequently. The hot corrosion test procedure used in this study is similar to the one reported by many researchers ( Ref 1,[30][31][32]. The thermo-gravimetric technique was used to establish kinetics of corrosion.…”
Section: Introductionmentioning
confidence: 97%